Pestle Analysis on Zero Waste Implementation in Crude Palm Oil Industries for Sustainable Development Concept - Azriadi, Emon; Frinaldi, Aldri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Nowadays, to match the dynamics of the marketplace and provide the expected product qualification, industrial manufacturing systems are always developing. One of the most issues which have a large influence on the product that would be accepted by the market is environmental issues. Implementing an environmentally friendly concept through the process could be one of the best solutions to counter the issue and it expectedly meets the requirement of the company's operational permit. In regards of the palm oil industry, is an essential source of national income and has an important role in creating opportunities for employment and developing rural areas in Indonesia, yet it also potentially can cause natural environmental degradation. This means the production process of CPO should be in line with ecological guidelines and legislation that could be used to attain more beneficial impacts on global market competitiveness, social and economic development, and better impacts in maintaining the environment as well. This research tried to critically evaluate the implementation of the zero waste technology scheme for Roundtable Sustainable Palm Oil (RSPO) mandatory in Crude Palm Oil (CPO) industries and its impact on the company's future position. Using PESTLE analysis then, it can recommend the best possible ways to treat the waste as an excess of the production process